ANALISIS FAKTOR RISIKO PAPARAN PESTISIDA TERHADAP KEJADIAN HIPERTENSI PADA PETANI BAWANG MERAH - Chyntia Nur Aviva Hidayat; Onny Setiani; Nikie Astorina Yunita Dewanti; Yusniar Hanani Darundiati (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2023)
The high use of pesticides can cause health problems, one of which is disorders of the sympathetic nervous system in regulating blood pressure. The preliminary study on 1-2 June 2022 in Wanasari and Jagalempeni Villages found that farmers use pesticides not according to the dosage set, and 14 out of 20 farmers experienced hypertension. This study aimed to analyze the risk factors of pesticide exposure to hypertension incidence in shallot farmers in Wanasari District, Brebes Regency. The research used a cross-sectional design. The research sample was 101 male shallot farmers in Wanasari and Jagalempeni Villages, taken by consecutive sampling technique. Data analysis used the chi-square test. The results showed that 62 (61,4%) respondents had hypertension, an average length of work of 5,01 hours/day, 3,72 types of pesticides, 2,76 times/week of spraying frequency, and 2,98 types of use of personal protective equipment (PPE). The statistic test showed that proven factors as risk factors of hypertension incidence were the length of work (p=0,003; PR = 4,048; 95% Cl = 1,650-9,928), pesticide dose (p=0,006; PR = 4,219; 95% CI = 1,578-11,281), spraying frequency (p=0,007; PR = 3,581; 95% Cl = 1,491-8,602), use of PPE (p=0,001; PR = 7,212; 95% Cl = 2,516-20,678), while the types of pesticides is not a risk factor of hypertension incidence. This research concluded that length of work, pesticide dosage, spraying frequency, and use of personal protective equipment (PPE) are the risk factors of pesticide exposure to hypertension incidence.